2007
DOI: 10.1093/ajcn/86.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospholipid and dietary fatty acids as predictors of type 2 diabetes: interpreting the role of linoleic acid

Abstract: Background: Dietary fatty acids may be associated with diabetes but are difficult to measure accurately. Objective: We aimed to investigate the associations of fatty acids in plasma and diet with diabetes incidence. Design: This was a prospective case-cohort study of 3737 adults aged 36 -72 y. Fatty acid intake (/kJ) and plasma phospholipid fatty acids (%) were measured at baseline, and diabetes incidence was assessed by self-report 4 y later. Logistic regression excluding (model 1) and including (model 2) bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
220
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(251 citation statements)
references
References 38 publications
25
220
4
2
Order By: Relevance
“…Several circulating fatty acids (e.g., 15:0, 17:0) have been suggested as biomarkers of dairy consumption (17)(18)(19), and they were reported to be associated with lower risk of diabetes (20,21) or cardiovascular disease (22,23). Previously, we found that erythrocyte trans-18:1 isomers are associated with dairy product consumption and lower prevalence of metabolic syndrome and diabetes in middle-aged and older Chinese men and women (24).…”
mentioning
confidence: 71%
“…Several circulating fatty acids (e.g., 15:0, 17:0) have been suggested as biomarkers of dairy consumption (17)(18)(19), and they were reported to be associated with lower risk of diabetes (20,21) or cardiovascular disease (22,23). Previously, we found that erythrocyte trans-18:1 isomers are associated with dairy product consumption and lower prevalence of metabolic syndrome and diabetes in middle-aged and older Chinese men and women (24).…”
mentioning
confidence: 71%
“…On the other hand, changes in saturated and monounsaturated fatty acids with respect to insulin resistance were lipoprotein-specific. Epidemiological prospective studies have shown that high proportions of esterified palmitic and stearic, and low proportions of esterified linoleic fatty acids in serum are risk factors for type 2 diabetes [33][34][35], myocardial infarction [36,37], the metabolic syndrome [38] and overall and cardiovascular mortality [39]. The relationship between the amount of polyunsaturated fat in the diet and the respective proportions of serum esterified polyunsaturated fatty acids is strong [40,10].…”
Section: Discussionmentioning
confidence: 99%
“…The implication of FA, particularly, omega-3 and -6 in different diseases has been widely published in literature [2][3][4][5][6][7][8][9]. SFA, abundantly found in our diet, participate in the development of certain metabolic abnormalities such as insulin resistance or atherosclerosis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this class of fatty acids probably contributes to the development of atherosclerotic plaques because it causes increased plasma concentrations of LDL-cholesterol [12]. All of this knowledge means that the current intake of SFA in western food, and in particular, palmitic acid, is a key player in the expansion of certain metabolic diseases such as type 2 diabetes, cardiovascular disease or metabolic syndrome [8,14]. Dietary long-chain, polyunsaturated fatty acid (PUFA) also benefit the blood vessel wall by enhancing cell membrane fluidity and regulating membrane receptors [15].…”
Section: Introductionmentioning
confidence: 99%